The Relationship between Serum Bimarkers with the Results of Down Syndrome Screening and Fetal Karyotype in High Risk Pregnant Women: Relationship Some serum biochemical markers with the results of first trimester Down syndrome screening - Sadat Hejazi-Shishavan, Fatemeh; Farshbaf-Khalili, Azizeh; Mahdipour, Mahdi; Abbasalizadeh, Fatemeh; Shahnazi, Mahnaz (Advances in Nursing & Midwifery, 2022)
Abstract Introduction: Considering the many problems of a child with Down syndrome, early diagnosis allows parents to prepare for the birth and care of these children or to suggest termination of pregnancy. This study aimed to investigate associations between serum levels of folic acid and Superoxide dismutase (SOD1) with the results of the first trimester Down syndrome screening and fetal karyotype in high-risk pregnant women. Methods: In this cross-sectional study, 232 women with high-risk pregnancies who had positive Down syndrome screening and undergone amniocentesis were selected through purposive sampling at the gestational age of 14-20 weeks. After obtaining an informed written consent form, the questionnaires related to the research were filled and the information on NT ultrasound and biochemical screening tests was extracted from the patients’ files. We measured serum levels of folic acid and SOD1 in all participants using the ELISA method. Statistical analysis was done by applying a multivariate logistic regression model by backward strategy. The Hosmer-Lemeshow test was utilized for better goodness of fit for the logistic regression model. In this study, p-value of <0.05 was considered statistically significant. Results: In our study, 97% of participants consumed folic acid, serum level measurements revealed, 6.9% of participants had low folic acid levels, and 5.6% of Down syndrome positive screenings had a positive karyotype. The mean (SD) serum levels of superoxide dismutase enzyme (SOD-1) measured in the present study in the participants was 297.40 (75.55) U/ml. There were no significant relationship between serum levels of folic acid [odds ratio (OR) (95% CI): 0.125 (0.001 to 31.42); P=0.461] and SOD1 levels [OR (95% CI): 0.99 (0.976 to 1.01); P=0.799] with fetal karyotype results (P>0.05). Conclusions: These findings demonstrate that serum folic acid and SOD1 concentration is not the predictive markers of Down syndrome karyotype in high-risk pregnant women who have positive Down syndrome screening through a double marker test.